2014
DOI: 10.1163/15685411-00002800
|View full text |Cite
|
Sign up to set email alerts
|

Comparative susceptibility of Macrotermes bellicosus and Trinervitermes occidentalis (Isoptera: Termitidae) to entomopathogenic nematodes from Benin

Abstract: The differential susceptibility of two termite species, Macrotermes bellicosus and Trinervitermes occidentalis, to four entomopathogenic nematodes (EPN) isolates from Benin, Heterorhabditis indica Ayogbel, H. sonorensis Azohoue2, H. sonorensis Ze3 and Steinemema sp. Bembereke, was bio-assayed in laboratory tests. Soldiers of both M. bellicosus and T. occidentalis were similarly susceptible, but more susceptible than workers. Forty-eight h post-exposure of workers of M. bellicosus to 50 infective juveniles (IJ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
1
12
1
Order By: Relevance
“…[48,105] reported that the prevalence of infective juveniles (IJs) of EPNs in different habitats is affected by both intrinsic (behavioral, physiological, and genetic characteristics) and extrinsic (antibiotics, competition, natural enemies, temperature, soil moisture, pH, soil type, soil texture, relative humidity, UV radiation, and desiccation) factors. For experimental purposes, performance of EPNs is known by studying their ability to withstand conditions of drought, lack of oxygen, tolerance to heat [38,106], capacity to search for targeted pests in the soil at specific concentration [107], to kill them, and to multiply inside them. The nematodes' tolerance to biotic factors is also studied under laboratory conditions.…”
Section: Environmental Stresses and Their Effect On The Performance Omentioning
confidence: 99%
See 2 more Smart Citations
“…[48,105] reported that the prevalence of infective juveniles (IJs) of EPNs in different habitats is affected by both intrinsic (behavioral, physiological, and genetic characteristics) and extrinsic (antibiotics, competition, natural enemies, temperature, soil moisture, pH, soil type, soil texture, relative humidity, UV radiation, and desiccation) factors. For experimental purposes, performance of EPNs is known by studying their ability to withstand conditions of drought, lack of oxygen, tolerance to heat [38,106], capacity to search for targeted pests in the soil at specific concentration [107], to kill them, and to multiply inside them. The nematodes' tolerance to biotic factors is also studied under laboratory conditions.…”
Section: Environmental Stresses and Their Effect On The Performance Omentioning
confidence: 99%
“…Most of the experiments designed in this regard are conducted using the larvae of the greater wax moth Galleria mellonella Linnaeus (Lepidoptera: Pyralidae), a model insect for EPN biology and pathogenicity studies [108]. Nematode isolates that perform best under laboratory conditions are then taken to semi-controlled and fields conditions [31,36,45] and tested against insect pests in biological control programs [31,36,106,109,110]. Grewal et al [111] observed greatest performance of indigenous EPN isolates as compared to exotic ones for the control of insect pests for being used in their natural environment.…”
Section: Environmental Stresses and Their Effect On The Performance Omentioning
confidence: 99%
See 1 more Smart Citation
“…Phoresis or other external contamination of animals is the most widely considered explanation for rapid short-range dispersal (Jabbour & Barbercheck, 2008) or long-range dispersal over several hundred meters or kilometres (Barratt, Blossey, & Hokkanen, 2006). Several types of soil invertebrates have potential to act as phoretic hosts for EPN, including earthworms (Campos-Herrera, Trigo, & Gutierrez, 2006;Shapiro, Tylka, Berry, & Lewis, 1995), isopods (Eng, Preisser, & Strong, 2005), predatory carabid beetles (Mertz, Agudelo, Sales, Rohde, & Moino, 2014) and termites (Zadji, Baimey, Afouda, Moens, & Decraemer, 2014). However, only insects capable of flight will result in significant displacement of EPN from the site of application.…”
Section: Persistence and Spread Of Populationsmentioning
confidence: 99%
“…Phoresis or other external contamination of animals is the most widely considered explanation for rapid short-range dispersal or long-range dispersal over several hundred meters or kilometres (Barratt, Blossey, & Hokkanen, 2006). Several types of soil invertebrates have potential to act as phoretic hosts for EPN, including earthworms (Campos-Herrera, Trigo, & Gutierrez, 2006;, isopods , predatory carabid beetles (Mertz, Agudelo, Sales, Rohde, & Moino, 2014) and termites (Zadji, Baimey, Afouda, Moens, & Decraemer, 2014). However, only insects capable of flight will result in significant displacement of EPN from the site of application.…”
Section: Persistence and Spread Of Populationsmentioning
confidence: 99%